Nasofrontal Mucocele Following after Craniotomy Procedure - Hutagalung, Tommy Rizky; Mouza, Abdurrahman (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2020)
Introduction : Mucocele is a chronic, expanding, mucosa-lined lesion of the paranasal sinus characterized by mucous retention that can be infected becoming a mucopyocele. They originate from obstruction of the sinus ostium by congenital anomalies, infection, inflammation, allergy, trauma (including surgery) or a benign or malignant tumor. The frontal sinuses are most commonly affected, and subsequently ethmoidal sinuses. Case Report : A 56 years old man, presented with a lump on the left and right forehead accompanied by a protruding left eye since 6 months and is getting wors. Patient with a history of craniectomy debridement surgery indicated for open depressed fracture due to an accident 12 years ago, then underwent a titanium mesh cranioplasty 11 years ago. From examination of the head CT scan revealed a solid mass lesion filling the left and right frontal sinuses expands into the left orbital cavity. Bifrontal craniotomy was performed on the patient. Discussion : Mucoceles are mucous-secreting expansive pseudocystic formations, and capable of expansion by virtue of a dynamic process of bone resorption and new bone formation. They result from obstruction of a sinus ostium and frequently are related to a previous condition as chronic sinusitis, trauma, surgery or expansible lesion. With continued secretion and accumulation mucus, the increasing pressure causes atrophy or erosion of the bone of the sinus, allowing the mucocele to expand in the path of less resistance. This may be into the orbit, adjacent sinuses, nasal cavity, intracranial or through the skin; intracranial and orbital extension were demonstrated in this patient. Conclusion : Frontal mucoceles are benign and curable, but early diagnosis and treatment of them is important. Open surgery remains a valid procedure in frontal mucoceles with orbital and/or intracranial extension and in cases where the district anatomy is unfavourable for a purely endonasal approach.